Frequency of Depression Among Females Underwent Hysterectomy in a Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: The objective of this study is to assess the frequency of depression among females underwent hysterectomy in a tertiary care hospital.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Saidu Teaching Hospital, Swat from 01/Jan/2023 to 30/June/2023.Methods: Through non-probability consecutive sampling, 180 women aged 20-70 years, any parity presented during follow-up period after hysterectomy within 1 year were included in the present study.Results: The mean Beck Depression Inventory (BDI) score among participants was 10.6 ± 2.1, with 108 participants categorized as depressed and 72 as not depressed. Age stratification showed a highly significant association with depression (p<0.0001). Parity stratification also showed a significant association with depression (p<0.0001).Conclusion: This study shows that depression is an issue that is common among women who undergo hysterectomy, most especially the young women and those with low number of children.